2015
DOI: 10.3390/ijms160818976
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Aspects of Tolerance to Environmental Constraints in Grain and Forage Legumes

Abstract: Despite the agronomical and environmental advantages of the cultivation of legumes, their production is limited by various environmental constraints such as water or nutrient limitation, frost or heat stress and soil salinity, which may be the result of pedoclimatic conditions, intensive use of agricultural lands, decline in soil fertility and environmental degradation. The development of more sustainable agroecosystems that are resilient to environmental constraints will therefore require better understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 245 publications
(304 reference statements)
2
38
0
1
Order By: Relevance
“…Indeed, under salty conditions, sustaining ion homeostasis is one of the adaptive strategies that tolerant plants use to cope with salt stress. These strategies may help the plant to prevent potentially toxic effects of the build-up of ions like Na + and Cl − that cause various types of damage to lipids, proteins and nucleic acids (Zhu and Gong, 2014;Bargaz et al, 2015;Rizwan et al, 2015). Application of 5 mM proline in a foliar spray decreased Na + content and increased K + /Na + ratio in P. vulgaris (Abdelhamid et al, 2013).…”
Section: Proline Treatment Mediates Reduction In Ion Toxicity Due To mentioning
confidence: 99%
“…Indeed, under salty conditions, sustaining ion homeostasis is one of the adaptive strategies that tolerant plants use to cope with salt stress. These strategies may help the plant to prevent potentially toxic effects of the build-up of ions like Na + and Cl − that cause various types of damage to lipids, proteins and nucleic acids (Zhu and Gong, 2014;Bargaz et al, 2015;Rizwan et al, 2015). Application of 5 mM proline in a foliar spray decreased Na + content and increased K + /Na + ratio in P. vulgaris (Abdelhamid et al, 2013).…”
Section: Proline Treatment Mediates Reduction In Ion Toxicity Due To mentioning
confidence: 99%
“…A more comprehensive approach was initiated by Subbarao et al [11] who found that consideration of individual morphological characteristics or physiological processes is not able to improve yield in new varieties of pulse crops in soil drought conditions. Bargaz et al [12] report that visible progress in adaptation of pulse plants to limited drought stress involves multigene-controlled traits. Due to the growing trend in Europe towards promotion of pulse crops in sustainable agriculture, different methods of raising the tolerance of plants to drought stress, not necessarily leading to genomic changes, are continually sought [13].…”
Section: Digital Signaturementioning
confidence: 99%
“…The lack of significant response in R d with additional N but without additional phosphorus (P) suggests the co-limitation of N and P in controlling R d (van De Weg et al 2013;Heskel et al 2014). The warming-induced decline in available P in grassland ecosystem (Geng et al 2017) thus, might explain the higher relative N reduction in IB than other species since legumes are sensitive to P deficiency (Bargaz et al 2015).…”
Section: Discussionmentioning
confidence: 99%